2019
DOI: 10.3177/jnsv.65.s222
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Colonic Fermentation of Sorghum (<i>Sorghum bicolor</i> L.): Important Correlations Observed among the Physiological Parameters of Cecum, Liver, Adipose Tissue and Fasting Serum Lipid Profile

Abstract: High amylose corn starch (HAS), whole grain sorghum (S-Wh), refined sorghum (S-Rf) and acorn starch (CON) diets were fed to animals for 1 mo aiming to examine the physiological effects of resistant starch inclusion in the diet from grains. HAS exhibited significantly lower feed intake, final body weight, serum lipid profile with significantly higher cecal parameters and short chain fatty acid (SCFA) contents. S-Wh group exhibited significantly higher body weight, feed intake and serum lipid parameters compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…In a previous study by the authors, raw sorghum fed rats exhibited contrasting results to the current study, where body weight, visceral fat mass and cecal SCFA profile were similar to the CON group, while the major microbial members were found to be involved in resistant amino acid metabolism instead of RS [ 15 ]. In contrast, in this study genus Ruminococcus was found to be a key player in the sorghum fed rat cecal microbiota, well known to be able to utilize RS and dietary fiber [ 37 ].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In a previous study by the authors, raw sorghum fed rats exhibited contrasting results to the current study, where body weight, visceral fat mass and cecal SCFA profile were similar to the CON group, while the major microbial members were found to be involved in resistant amino acid metabolism instead of RS [ 15 ]. In contrast, in this study genus Ruminococcus was found to be a key player in the sorghum fed rat cecal microbiota, well known to be able to utilize RS and dietary fiber [ 37 ].…”
Section: Discussioncontrasting
confidence: 64%
“…Sorghum ( Sorghum bicolor L. Moench) is the fifth most cultivated cereal in the world and is known for its higher native RS content (12–21%) compared to other cereals [ 12 , 13 ]. Raw sorghum exhibited moderate colonic fermentation potential under in vitro and in vivo conditions as previously reported by the authors [ 14 , 15 ]. Cooking of sorghum has shown to increase the RS content due to decreased protein digestibility and enhanced strength of the amylose-lipid complex according to previous studies [ 13 , 16 , 17 ].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation